A new statistical model for longitudinal ecological momentary assessment data on dual use of electronic and combustible cigarettes. (3rd September 2022) - Yang, James; Kuo, Jacky; Su, Wei-Chung; Jorenby, Douglas E.; Piper, Megan E.; Buu, Anne
ABSTRACT: Background: Existing studies of dual use of electronic and combustible cigarettes either collected longitudinal data with long gaps in between waves or conducted ecological momentary assessment (EMA) over a short period of time. In recent years, the measurement burst design that embeds an EMA protocol in each wave assessment of a traditional longitudinal study has become more popular and yet conventional generalized linear mixed models (GLMM) have important limitations for handling data from this design. Objectives: This study proposed a new statistical method to analyze data from the measurement burst design. Methods: This new statistical method was designed to model the short-term (within-wave) as well as long-term (between-wave) changes and was validated by a simulation study. Secondary analysis was conducted to analyze data from 205 dual users (52% male) and 146 exclusive smokers (50% male) who participated in a recent study using the measurement burst design. Results: The simulation study shows that the proposed method can handle the gap between waves well and is also robust to nonlinear changes across waves. Although no short-term change in smoking was found, dual users reported a long-term reduction in cigarette use that was more rapid compared to exclusive smokers ( β ˆ = − 0.0127, p = .0167 ). Vaping more was associated with smoking less ( β ˆ = − 0.0058, p = .0054 ). Conclusion: The proposed method is highly applicable as it can be easily implemented by substance use researchers and the results can be straightforwardly interpreted. The results suggest that e-cigarette use may play a role in promoting a long-term reduction in smoking among dual users.